2023
DOI: 10.3390/rel14030366
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and the Perception of Interreligious Threats: The Suppressing Effect of Negative Emotions towards God

Abstract: Religiosity has been studied for its impact on other sociological and psychological aspects of society, particularly personal wellbeing and interpersonal relationships. However, it has yet to be studied for its impact on interreligious prejudice as measured by perceptions of interreligious threats. The present study investigates how religiosity (both positive and negative measures) affects perception of threats from other religious groups within the Malaysian context by using the Centrality of Religiosity Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Considering that the values obtained for kurtosis and skewness of the study variables were far below the suggested +2/−2 range, all variables appeared to be normally distributed [41]; thus, an adequate normal distribution was expected [42]. Furthermore, as far as regression and mediation analyses are concerned, the central limit theorem (CLT) assumes that, with a moderately high sample size, with reports as low as >200 [43], the distribution of residuals in the data will approximate ever greater normality [44,45].…”
Section: Descriptive Statistics and Correlationsmentioning
confidence: 99%
“…Considering that the values obtained for kurtosis and skewness of the study variables were far below the suggested +2/−2 range, all variables appeared to be normally distributed [41]; thus, an adequate normal distribution was expected [42]. Furthermore, as far as regression and mediation analyses are concerned, the central limit theorem (CLT) assumes that, with a moderately high sample size, with reports as low as >200 [43], the distribution of residuals in the data will approximate ever greater normality [44,45].…”
Section: Descriptive Statistics and Correlationsmentioning
confidence: 99%
“…In addition to materialist matters (e.g., unemployment, economic competition, etc. ), a great deal of research has also been sensitive to the ways in which boundary making and collective identification connect to ideational dimensions, such as race, religion, nationhood, language, and culture (Wimmer 2008;Sarjoon et al 2016;Lubbers and Coenders 2017;Gorman and Seguin 2018;Lam et al 2023).…”
Section: Reactive Identificationmentioning
confidence: 99%